Economic Perspectives of Trademarks - Chapagai, Rishi Ram (Saptagandaki Journal, 2018)
Primarily, this paper examines the role of trademark in global economy, as an intellectual property the value of trademark and brand in the global marketplace, and the economic potentiality of trademarks to generate more value and surplus in the economy. This paper also discusses the contribution of the trademarks for creating brand and value of business enterprises. The article is basically conceptual and descriptive in nature. Based on the literature review, the purposes of this paper are; to assess the perceived value of a trademark and brand, to examine the trademark roles for creating brand and value and to understand the impact of trademark on economy. The article deals with trademark and its economic perspectives. This article is valuable to understand the value of trademark in marketplace. The article helps academicians and practitioner to know the concept of trademark as an intellectual property and to understand that it can be used by market economy to generate more income, value, and surplus in the economy. The economic perspective of trademark can be applicable to many segments of Nepalese business context; ranging from manufacturing to service sector and importantly for the entrepreneurship development. Finally, the article is recommending for further empirical research study to examine the impact of trademark protection system for the countries’ economic growth. The Sapta Gandaki Journal Vol. IX, 2018 Feb. Page: 73-83